Attentional control moderates the relationship between social anxiety and selective attentional responding to negative social information: evidence from objective measures of attentional processes. Issue 7 (3rd October 2021) - Mazidi, Mahdi; Grafton, Ben; Basanovic, Julian; MacLeod, Colin
ABSTRACT: Cognitive theories of social anxiety implicate greater attention to negative social information in the development and maintenance of heightened social anxiety. Empirical evidence for this proposal, however, has been inconsistent. The aim of the current study was to examine the role of attentional control, which is one's ability to deploy attention to goal-relevant information as a potential moderator of the association between selective attentional responding to negative social information and social anxiety. Eighty-nine adults were recruited through Mechanical Turk platform and completed the Social Interaction Anxiety Scale as well as a novel paradigm designed to measure selective attentional responding to negative social information (angry faces) and attentional control. Attentional control was operationalised as the capacity to direct attention to the specified target stimuli. The results supported the hypothesis that attentional control plays this moderating role. Specifically, while participants with low levels of attentional control exhibited a positive association between social anxiety and selective attentional responding to negative social information, this association was eliminated among participants with high levels of attentional control. This finding may explain the heterogeneity of research findings in this area. Implications, limitations and directions for future research are discussed.